A visually meaningful secure image encryption algorithm based on conservative hyperchaotic system and optimized compressed sensing - Tong, Xiaojun; Liu, Xilin; Pan, Tao; Zhang, Miao; Wang, Zhu (Multimedia systems, 2024)
Aiming at the traditional schemes for encrypting and transmitting images can be subject to arbitrary destruction by attackers, making it difficult for algorithms with poor robustness to recover the original image, this paper proposes a new visually image encryption algorithm, which can embed the compressed and encrypted image into a carrier image to achieve visual security, thus avoiding destruction and attacks. Foremost, a new conservative hyperchaotic system without attractors was constructed that can resist reconstruction attacks. Secondly, a two-dimensional (2D) compressed sensing technique is adopted, and the pseudo random sequences of the proposed chaotic system generates a measurement matrix in compressed sensing, and optimizes this matrix to improve the visual quality of image reconstruction. Finally, by combining discrete wavelet transform (DWT) and singular value decomposition (SVD) methods, the encrypted image is embedded into the carrier image to achieve the purpose of image compression, encryption, and hiding. And experimental results and comparative analysis demonstrate that this algorithm has high security, good image reconstruction quality, and strong imperceptibility after image embedding. Under limited bandwidth conditions, the algorithm achieves excellent visual security effects.